Agroecology on the periphery: A case from the Maya-Achí territory, Guatemala. Issue 7 (14th September 2019) - Einbinder, Nathan; Morales, Helda; Mier Y Terán-Giménez Cacho, Mateo; Aldasoro, Miriam; Ferguson, Bruce G.; Nigh, Ronald
ABSTRACT: In this paper we examine processes of scaling agroecological practices in the Maya-Achí territory of Guatemala. We compare the Achí case to other examples documented in the literature and the key factors, or "drivers, " reported as important if not essential for scaling to occur. We find that the Achí scase is complex with regard to these drivers. Factors such as constructivist learning/teaching methods, favorable public policies, and strong social fabric appear to be weak, absent, or even negative. This is due in part to the violence and repression of the 1980s, which resulted in the assassination of 20 percent of the population by the military and paramilitaries, leaving the territory socially fragmented. Projects incorporating agroecology (revalorization of ancestral practices, seed saving, elimination of external inputs, strengthening soil health, increasing/guarding agrobiodiversity) are viewed as a potential strategy to aid in community recovery, and are promoted by local associations as well as by international institutions and NGOs. While social and cultural recuperation were initially hypothesized as primary causes for the adoption of practices, we encounter a range of additional and complex factors, such as the expectation of economic benefits and the presence of aid and development organizations. By analyzing these drivers and barriers we contribute to the ongoing debate over how agroecological practices may be scaled-out, particularly in regions exhibiting less than ideal conditions.